Thermal Properties of Ionic Liquids and Ionanofluids - Ribeiro, A.P.C.; Vieira, S. I. C.; França, J. M.; Queirós, C. S.; Langa, E.; Lourenço, M. J. V.; Murshed, S. M. S.; Castro, C. A. Nieto de (IntechOpen, 2011)
None